1984
DOI: 10.1246/bcsj.57.759
|View full text |Cite
|
Sign up to set email alerts
|

An Electrochemical Study on Anion Doping-Undoping Process of Polyacetylene by Means of FFT Impedance Measurement

Abstract: An electrochemical anion doping-undoping process of cis-polyacetylene, (CH)x, was investigated in 1 mol dm−3 LiClO4 or LiBF4 in propylene carbonate by the FFT impedance measurement. This could be applied to the system with time-variation because of its high speed measuring duration. The doping-undoping process of the anion was represented by the Randles-type equivalent circuit, considering the corrective term concerned with surface roughness. The impedance behavior of the doping-undoping process was pursued by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…For an input current signal at high frequencies of 5.0 Hz and 50 Hz, EIS was carried out using a square current input with a Fourier transform, as detailed in [15] and [16]. The peak-to-peak amplitude and base current (offset current) were 800 mA and 600 mA, respectively.…”
Section: Square Current Eismentioning
confidence: 99%
See 1 more Smart Citation
“…For an input current signal at high frequencies of 5.0 Hz and 50 Hz, EIS was carried out using a square current input with a Fourier transform, as detailed in [15] and [16]. The peak-to-peak amplitude and base current (offset current) were 800 mA and 600 mA, respectively.…”
Section: Square Current Eismentioning
confidence: 99%
“…It was reported that white noise [11,12], pseudo-random noise (pseudo-white noise) [12][13][14][15][16][17], pseudo-random signals [18], multi-sine waves (superimposed sine waves) [19,20], step signals [10,12,[21][22][23][24][25], and square pulses [26,27] can be applied to FFT impedance. An on-line FFT impedance measurement system using pseudo-white noise as the input signal was developed by one of our authors [14,15], and its application to in situ EIS was reported [15][16][17]. AC voltammetry has been widely used for electrochemical analysis [35,36].…”
Section: Introductionmentioning
confidence: 99%
“…The hydrophobic interaction occurs between the hydrophobic tail of SDS and bulky ligand of metal complexes has predominance over the electrostatic interaction and the hydrophobic interaction is related to the type of ligand involved. Tachiyashiki et al [19] have commented that the interaction of the Fe(II) complexes with CTAB is predominantly hydrophobic and also mentioned a strong interaction of quaternary ammonium head group with π-electron system of aromatic groups of the ligands in the iron(II) complex is also quite significant. Oldega et al [20] They reported that hydrophobic interaction is more significant and lowers CMC more than electrostatic interaction.…”
Section: Effect Of Metal Complexes On the Micellar Properties Of Sdsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12]17,[25][26][27][28] The conventional EIS measured by a frequency response analyzer (FRA) and potentiostat system is a powerful tool to check the state of LIBs (i.e. SOC and SOH).…”
Section: Square Current Electrochemical Impedance Spectroscopymentioning
confidence: 99%
“…The first stage of our work on the EIS focused on electrochemical reactions of electroconducting polymers. [7][8][9][10] At the same time, Professor Su-Moon Park also investigated electroconducting 158 Tetsuya Osaka, Hiroki Nara, Daikichi Mukoyama, and Tokihiko Yokoshima polymers by means of the EIS. 11,12 In addition, Professor Su-Moon Park [13][14][15] and our team 9,16,17 worked in the same field of electroconducting polymers prior to working on the EIS.…”
Section: Introductionmentioning
confidence: 99%